Seafood: a key feature of the mediterranean diet - Aníbal, J. (2017)
The Mediterranean Diet is based on three pillars: bread, olive oil and wine. These food products supply carbohydrates and lipids to the diet, but they lack proteins. Traditionally, in the Mediterranean Diet three meals per week should include seafood to contribute to the specified protein dietary requirements. Seafood is “any form of sea life regarded as food by humans”, and prominently includes fish, shellfish, and edible sea plants. In some countries, the term also includes freshwater organisms. Seafood is a good source of essential amino acids, such as phenylalanine and tryptophan, and of essential fatty acids, particularly omega-3 and omega-6.